Baylis–Hillman Adducts as a Valuable Source for Synthesis of Functionalized [4,4,4]-Propellone Dilactone Derivatives - Malvi, Payal; Mistry, Dharti; Karunakar, Galla V.; Rajput, Diksha; Lenin, Dandamudi V. (Synlett, 2025)
A simple and facile synthesis of functionalized [4,4,4]-propellone dilactone derivatives through dialkylation of cyclic 1,3-diketones with Baylis–Hillman adducts and subsequent dilactonization is described. This methodology is appealing because it is reliable and scalable (the products can be synthesized on a gram scale). The tricyclic products can be exploited for their biological activity.
Keywords: Baylis–Hillman adducts; propellones; cyclic diketones; alkylation; lactonization